Penularan Virus Bergejala Mosaik Pada Tanaman Melon (Cucumis melo L.) Secara Mekanis dan Melalui Vektor Kutu Daun - MISBAHUL KHULUQ; TRISNA AGUNG PHABIOLA; I NYOMAN WIJAYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Transmission of Symptomatic Mosaic Virus in Melon (Cucumis melo L.)Mechanically and Through the Aphids Vector Melon (Cucumis melo L.) is one of the horticulture plants that is widely cultivated and consumed by the people of Indonesia. But the decrease in yield due toan OPT attack (plant disrupting organisms) is a major concern. Among the pests thatplay a role in reducing the yield of melons are viruses and insect vectors. Aside frombeing a pest, aphid insect also act as vector transmitters of viruses that cause mosaicsin melon plants. The method of transmission in this research used the method oftransmission mechanically and through aphids vectors. The aim of this research wasto examine the potential transmission of Potyvirus wich caused mosaic on melonmechanically and through the vector Aphis gossypii. The parameters are the type ofsymptoms, the percentage of the disease and the intensity of the disease attack. Thevariations of symptoms showen were dark green mosaic patterns, yellow mosaicpatterns, vein-banding and malformations. The results of the transmission test wereproven by molecular identification using the Reverse Transcription Polymerase ChainReaction method. The results explained that the Potyvirus could be transmittedmechanically with disease incidence of 100%, disease intensity of 42% and throughAphis gossypii vector with a disease incidence of 90%, disease intensity of 28%. Thetest was proven using the RT-PCR method with CIFor and CIRev primers whichshowed amplicon product 700 pb.